FORMULASI SEDIAAN SIRUP SARI BUAH SENGGANI (Melastoma malabathricum L.) - Tri Yanuarto; Devi Novia; Septi Putri Lestari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Senggani fruit (Melastoma malabathricum L.) is one of the wild plants whose leaves are usually used by the community as a medicine for wounds and cancer sores. Senggani fruit contains high anthocyanins and antioxidants, which are very good for preventing cancer in the body. The purpose of this research is to make syrup of Senggani fruit juice. The formulation of Senggani fruit juice syrup was made by heating method at 54Â°C with various concentrations of F0, F1 (5%), F2 (6%) and F3 (8%). Then, the physical properties were tested, namely organoleptic, viscosity test, pH test, homogenity test, hedonic test and descriptive test. From testing the physical properties of the syrup formulation of Senggani fruit, it was found that the organoleptic test of F2 and F3 showed a change in consistency; for the pH test results the four formulas ranged from 3.98 to 7.07; the homogeneity test on F2 and F3 was not homogeneous, there were black grains at the 3rd week; then the viscosity test of syrup preparations F2 and F3 obtained an average result of 30 - 51.33 cPs; as well as hedonic and descriptive tests with the criteria of somewhat like - like the most preferred is F3.